The glycine arginine-rich domain of the RNA-binding protein nucleolin regulates its subcellular localization - Doron-Mandel, Ella; Koppel, Indrek; Abraham, Ofri; Rishal, Ida; Smith, Terika P; Buchanan, Courtney N; Sahoo, Pabitra K; Kadlec, Jan; Oses-Prieto, Juan A; Kawaguchi, Riki; Alber, Stefanie; Zahavi, Eitan Erez; et al. (The EMBO journal, 2021)
Nucleolin is a multifunctional RNA Binding Protein (RBP) with diverse subcellular localizations, including the nucleolus in all eukaryotic cells, the plasma membrane in tumor cells, and the axon in neurons. Here we show that the glycine arginine rich (GAR) domain of nucleolin drives subcellular localization via protein-protein interactions with a kinesin light chain. In addition, GAR sequences mediate plasma membrane interactions of nucleolin. Both these modalities are in addition to the already reported involvement of the GAR domain in liquid-liquid phase separation in the nucleolus. Nucleolin transport to axons requires the GAR domain, and heterozygous GAR deletion mice reveal reduced axonal localization of nucleolin cargo mRNAs and enhanced sensory neuron growth. Thus, the GAR domain governs axonal transport of a growth controlling RNA-RBP complex in neurons, and is a versatile localization determinant for different subcellular compartments. Localization determination by GAR domains may explain why GAR mutants in diverse RBPs are associated with neurodegenerative disease.
Keywords: axonální transport; Axonal Transport; sekvence aminokyselin; Phosphoproteins; subcellular localization; lidé; Mice, Inbred BALB C; protein-membrane interaction; HeLa Cells; Gene Expression; kineziny; Cell Line, Tumor; fosfoproteiny; RNA-Binding Proteins; messenger RNA; RNA, Messenger; Mutation; Neurons; Nucleolin; myši; Cell Nucleolus; Humans; local translation; neurony; Mice; nervus ischiadicus; mutace; Protein Domains; Ganglia, Spinal; axonal transport; nukleolin; HEK293 buňky; mužské pohlaví; Primary Cell Culture; Sciatic Nerve; myši inbrední BALB C; primární buněčná kultura; zvířata; Mice, Inbred C57BL; HeLa buňky; spinální ganglia; proteiny vázající RNA; buněčné jadérko; Animals; exprese genu; cell size regulation; nádorové buněčné linie; Male; proteinové domény; Kinesins; Amino Acid Sequence; HEK293 Cells; myši inbrední C57BL